Balancing paid work and personal life coping mechanisms of men and women in the academe - Samson-Quintillan, Lynette (2010)
This case study delves on gender differences in coping mechanisms to achieve paid work (PW) and personal life (PL) balance. It involves 145 men and 205 women employees of the University of the Philippines (UP) Diliman. It aims to identify coping mechanisms adopted by UP Diliman workers, their PW-PL issues and concerns, and factors that affect their manner of coping. Using a triangulated approach involving organisational ethnography and survey method, minimal gender differences are observed. Results likewise reveal gender differentials in terms of PW-PL issues and concerns, time management and spending habits, values and goals in life, and views about coping, the importance of PW-PL balance role of the workers union, and UP's HR-related policies.

Although employment conditions are far from perfect, many UP Diliman survey respondents are able to cope with demands of their PW-PL roles. Moreover, their manner of coping is affected by enabling factors, such as personality, values and goals in lief, social support, availability of resources, culture, and institutional policies, as well as efforts by the workers union. Hindering factors involve zero or limited access to resources and workplace policies that provide better employment incentives. Based on the findings, policy recommendations and courses of action are offered which include:modifying existing policies on certain benefits (e.g. housing and healthcare), advocating for the ratification of International Labor Organization (ILO) Convention 102 to impel the Philippine government to enact a law on unemployment and family benefits, and establishing a UP Work-Life Resource Center and a National Work-Life Institute.
Keywords: Work-life balance; Quality of work life; University of the Philippines (Diliman)